Ultrasensitive and Cost-Effective Detection of Neuropeptide-Y by a Disposable Immunosensor: A New Functionalization Route for Indium-Tin Oxide Surface - İnci Uludağ; Mustafa Kemal Sezgintürk (Biosensors, 2022)
Neuropeptide Y (NPY) is one of the most abundant neuropeptides in the human brain, and its levels in the blood change in neurodegenerative and neuroimmune disorders. This indicates that NPY may serve as a diagnostic and monitoring marker for associated disorders. In this paper, an electrochemical immunosensor was created to detect NPY biomarkers using a novel immobilization technique. The proposed biosensor system enables accurate, specific, cost-effective, and practical biomarker analysis. Indium tin oxide-coated polyethylene terephthalate (ITO-PET) sheets were treated with hexamethylene diisocyanate (HMDC) to covalently immobilize antibodies. Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) techniques were used to analyze each step of the biosensors. The proposed NPY biosensor has a broad linear detection range (0.01–100 pg mL−1), a low limit of detection (LOD) (0.02968 pg mL−1), and a low limit of quantification (LOQ) (0.0989 pg mL−1). Atomic force microscopy (AFM) was used to support in the optimization process, study the surface morphology, and visualize it. Studies of repeatability, reproducibility, storage, and Kramers–Kronig transformation were conducted during electrochemical characterization. After analytical experiments, the biosensor’s responses to human serum samples were evaluated. According to the obtained data, the error margin is small, and the created biosensor offers a great deal of promise for the clinical measurement of NPY.